Knowledge Awareness and Perception towards Prosthodontics Treatment and Services among Medical Students in Jeddah City, Saudi Arabia- A Cross Sectional Pilot Study: Pharmaceutical Science-Prosthodontics for Dental Health - Dr Karunakar Shetty; Fatima Alzahra Ansari; Nada Ibrahim Alzurqi; Arwa Ahmed Althagafi; Raniyah Abualnour (International Journal of Life Science and Pharma Research, 2022)
Prosthodontics is concerned with the design, manufacture and fitting of artificial replacements for teeth and other parts of the mouth. Prosthodontic treatment involves the replacement of missing teeth by means of removable or fixed partial denture, implants, complete dentures, or over dentures. The aim of this study was to evaluate the level of knowledge, perception, awareness and attitude of the medical students towards Prosthodontic treatment. A cross-sectional, Questionnaire based study was conducted among Medical students, covering various Medical colleges in Jeddah city. The study population was selected using cluster random sampling. Altogether 151 undergraduate medical students throughout Jeddah city participated in this study. The data was collected, compiled, and statistically analyzed using SPSS software version 21 and Chi-square test, t-test, and ANOVA. was performed A total of 151 participants, out of which there were 88 female participants (58.3%) and 63 male participants (41.7%), completed and returned the questionnaire. 134 participants (88.7%) were aware that missing teeth could be replaced and 17 participants (11.3%) were unaware. 93 participants (61.6%) felt implant Supported Prosthesis is a better Option for replacement of missing teeth and 58 participants (38.4%) did not feel so. 75 participants (49.7%) chose fixed partial denture as an option for replacement of missing teeth whereas 76 participants (50.3%) opted for removable partial denture. 64 participants (42.4%) had fear of prosthodontic replacement and 87 participants (57.6%) had no fear. Within the limitations of this study, following conclusions were drawn: Majority of the medical students was aware that missing teeth could be replaced. Most of them thought Implant supported prosthesis would be a better option for replacing missing teeth. Equal number of participants opted for fixed prosthesis. The most important finding of this study was that majority of the participants showed a lack of knowledge regarding oral hygiene measures with dental prosthesis.